Mining Claim Disputes in Québec - Lacasse, Jean-Paul (Revue générale de droit)

(untitled) (Éditions de l’Université d’Ottawa, 1986)
Mining claim disputes in Québec generally arise either when more than one staker carries out simultaneous stakings on the ground or when one or more stakers, while disputing the validity of a claim already recorded, under The Mining Act, stake the same piece of ground.Applications for record that give rise to a dispute are referred to the Minister of Energy and Resources. He may in turn refer the case to the Mining Judge. If he chooses not to do so, an appeal of his decision, by the party whose claims are refused or cancelled, lies with the Mining Judge. Decisions of the Mining Judge may be appealed to the Court of Appeal.Provisions of The Mining Act relating to the method ot staking are compulsory and entail, for instance, that block staking is illegal and that staking must be done personally.If the staker of a recorded claim has not staked his claim according to the Act and has declared in his notice of staking that he followed the Act, then the claim was recorded under misrepresentation and may be cancelled. However, a limitation exists in favour of a third-party holder in good faith when the claim has been recorded in his name for a year.Under the doctrine of substantial compliance, the staker may depart from the staking provisions of the Act in varying degree according to circumstances requirements. Applications of the doctrine to various situations of fact include non substantial discrepancies as to the area of the claim or the location of posts.Disputes may also relate to forfeiture and the re-opening of the land to staking. One may also dispute his own claims in order to prevent others from eventually disputing them if the claims had not been initially well staked. In the adjudicating process, it is important for the staker to be present at the hearing lest the other party be favoured.Disputes have provided for a better understanding of the Act's staking provisions. However, some drawbacks of the system would warrant changes to the Act for purposes of efficacy.